Developmental and molecular response of bovine embryos to reduced nutrients in vitro. Issue 1 (23rd December 2020) - Herrick, Jason R; Rajput, Sandeep; Pasquariello, Rolando; Ermisch, Alison; Santiquet, Nicolas; Schoolcraft, William B; Krisher, Rebecca L
Abstract : Recent studies in our laboratory have indicated that bovine embryos only use a small amount of the nutrients available to them in culture. Our objective was to evaluate the developmental and molecular response of bovine embryos when nutrient concentrations in the culture medium were significantly reduced. Following IVM and IVF, embryos were cultured in media containing 75, 50, and 25% (experiment 1) or 25, 12.5, and 6.25% (experiment 2) of the concentrations of nutrients (carbohydrates, amino acids, and vitamins) present in our control medium (100%). Blastocyst formation, hatching, and allocation of cells to the inner cell mass (ICM) and trophectoderm (TE) were evaluated on day 7. Although the number of TE cells was decreased ( P < 0.05) when nutrient concentrations were ≤25% (73.8–124.1 cells), it was not until nutrient concentrations were reduced to 6.25% that blastocyst formation (18.3 ± 3.0%) and hatching (3.0 ± 1.3%) were inhibited ( P < 0.05) compared to embryos cultured in the control medium (156.1 ± 14.1 cells, 40.0 ± 3.8%, 20.0 ± 3.1%, respectively). Inhibition of fatty acid oxidation (etomoxir) reduced ( P < 0.05) blastocyst development, with more pronounced effects at lower nutrient concentrations (≤12.5%). Reducing nutrient concentrations was associated with increased activity of AMPK, decreased activity of mTOR, and altered abundance of transcripts for hexokinase 1 ( HK1 ), carnitine palmitoyl transferase 2 ( CPT2 ), lactate dehydrogenase A ( LDHA ), and pyruvate dehydrogenase kinase 1 ( PDK1 ), consistent with an increase in glucose and fatty acid metabolism. Reduced nutrient conditions provide a unique perspective on embryo metabolism that may facilitate the optimization of culture media. Lay summary: To support early embryo development in the first week after fertilisation, an appropriate mixture of nutrients (carbohydrates, amino acids, and vitamins) is needed in the culturing solution. However, refining these solutions to support optimal embryo health remains challenging. In this study, bovine (cow) embryos derived from abattoir material were used as a model for the development of other mammalian embryos, including humans. These embryos were cultured in the presence of 75, 50, 25, 12.5, or 6.25% of the nutrients present in control conditions (100%), which are similar to those reported for the fluids of the fallopian tubes and uterus. Embryo development was largely unaffected in the 75, 50, and 25% treatments, with some embryos developing in the presence of only 6.25% nutrients. Cow embryos are remarkably resilient to reduced concentrations of nutrients in their environment because they can utilize internal stores of fat as a source of energy.